Pembelajaran Cerpen Dengan Metode Berbasis Masalah (Problem Based Learning) Pada Siswa SMP Negeri 2 Jumapolo Kabupaten Karanganyar - MUDMAINAH, MUDMAINAH; Prof. Dr. Ali, Imron Al-Ma'ruf; Prof. Dr. Abdul, Ngalim M.M (2016)
This study has three objectives. First, to describe the form of a short story by learning plan based methods problems (problem based learning). Second, to describe the implementation of short stories based methods of learning problems (problem based learning). Third, to find obstacles in learning stories with problem-based method (problem based learning). Fourth to describe the solution of problems with a short story based methods of learning problems (problem based learning). This research uses descriptive qualitative research strategy. The strategy used case studies. Data in the form of words, speech and learning behaviors, interviews, and field notes. Data sources include documents, school, activity or event, learning. Informants both teachers, principals, business facilities and infrastructure, curriculum and student affairs. The technique of collecting data through bservation, interviews and document analysis. Test the validity of data used triangulation data. This research receipts interactive model (interactive model of analysis af), namely reducing the data, presenting data, and draw conclusions. The first results of this study, lesson plan includes syllabi, lesson plans, teaching materials, methods penmbelajaran, learning resources, and evaluation of earning outcomes in junior high school district state 2 Jumapolo planned to complete. Second, the implementation of short stories based methods of learning problems (problem based learning) could take place, though not maximized. Third, the constraints encountered in the learning of a short story by a method based on problem (problem based learning) there are a few things, namely (1) the low input of students, (2) unmastered innovative method, (3) the unavailability of multimedia facilities, (4) spacious classrooms, (5) the limited book collection. Fourth, a solution that traveled there a few things, namely (1) include MGMPs, (2) seminar learning, (3) conduct supervision, (4) will complement the multimedia facilities, (5) use the media to the maximum, and (6) school add collection book collection.